From the History of the Research on Dostoevsky. The Legacy of Vasily Komarovich - Nikolai N. Podosokorsky (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The review is devoted to the edition of collected works by the outstanding scholar Vasily Komarovich (1894–1942), researcher of the life and work of Fyodor Dostoevsky, philologist, textual critic, and folklorist. Most of the articles included in the book were published in small editions during the author’s lifetime and have never been reprinted since then. The book also contains materials on Vasily Komarovich.